Web Monitoring CO, CO2 dan Suhu secara Real Time - Ahmad Zainuri; Gurum Ahmad Pauzi; Junaidi; Warsito (Journal of Energy, Material, and Instrumentation Technology, 2020)
This research is related to making a web to display data on CO, CO2 and temperature monitoring results in real time. The measuring instrument used consisted of an MQ-7 sensor to detect CO gas, a MQ-135 sensor to detect CO2 gas, a DHT-22 sensor to measure the temperature and a microcontroller as a control system. CO, CO2 and temperature measurements were carried out at the University of Lampung with 10 different points. Measurements were made for three days in the morning, afternoon and evening with the duration of measurement of each location 5 minutes. Measurement data is displayed on the PC server using an interface created through the Visual Basic 2010 program and saved to the Mysql database. Data from the database is sent to the web server. Based on the results of tests conducted, the web monitoring system is running well. The web can display CO, CO2 and temperature measurement data in the form of graphs and tables in real time. The web can be accessed by web browser at devices that are connected to the internet.